Conducting Critical Literature Reviews: A Methodological Note - Gheondea-Eladi, Alexandra (Calitatea Vieții, 2015)
In this paper a general view over literature reviews is given, as well as a short description of the possibilities of two of the current bibliographical referencing softwares available, EndNote and Mendeley. I argue that unlike other types of literature reviews, a critical literature review cannot be undertaken by writing notes and using the search engines of bibliographical referencing softwares, but by focusing on a judgment structure which evaluates the theoretical background of the papers, their assumptions and one that provides a logical structure of the paper. Such a judgment structure is likely to be used across many fields in the social sciences. The proposed judgment structure has been provided based on its applications in two different fields from the social sciences.